Anatomical Study of Arachnoid Granulation in Superior Sagittal Sinus Correlated to Growth Patterns of Meningiomas - Ye, Yuanliang; Gao, Wen; Xu, Weilin; Gong, Jiangu; Qiu, Minxing; Long, Lang; Ding, Jiuyang (Frontiers in Oncology, 2022)
Meningiomas in the parasagittal region were formed by arachnoidal cells disseminated among arachnoid granulations. The purpose of this study was to characterize the morphology of chordae willisii, and AGs found in the superior sagittal sinus. This study used 20 anatomical specimens. Rigid endoscopes were introduced via torcula herophili into the sinus lumen. The morphological features of arachnoid granulation and chordae willisii were analyzed, and then arachnoid granulations and chordae willisii were assessed by Elastic fiber stains, Masson’s stains, and imaging analysis. Three types of arachnoid granulations were present in the examined sinuses. There were 365 counts of arachnoid granulations in examined sinuses by imaging analysis, averaging 1.362.58 per sinus. Types I, II, and III made up 20.36%,45.23%, and 34.41% of 268 patients, respectively. Microscopy of chordae willisii transverse sections indicated the existence of a single layer and a multiple-layered dura sinus wall. The dural sinus wall was the thickest one in the superior sagittal sinus. The thickness of longitudinal lamellae was significantly greater than trabeculae. This study reveals the anatomical differences between arachnoid granulations in the superior sagittal sinus. The arachnoid granulations classification enables surgeons to predict preoperatively growth patterns, followed by safely achieving the optimal range of parasagittal meningioma resection.